E-learning and Web 2.0: a value creation perspective for global engagement - Wong, David; Kingshott, Russel; Loh, Claire (Korean Scholars of Marketing Science, 2012)
A model of student-faculty and student-student interactions using interactive Web 2.0 technologies in e-learning is offered and explained using literature from service-dominant logic research. This paper provides a fresh perspective with regard to how value is cocreated by both faculty and students through a set of experiences and interactions.